Die Flächentheorie im Raum mit dem verallgemeinerten euklidischen Zusammenhang - Bliznikas, V. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Близникас. Теория поверхностей пространства обобщенной евклидовой связностиV. Bliznikas. Apibendrinto euklidinio sąryšio erdvės paviršių teorija